Sensitivity of flood damage estimation to spatial resolution. (17th December 2015) - Komolafe, A.A.; Herath, S.; Avtar, R.
Abstract: Flood damage estimation is an important element in flood risk assessment; it is useful for mobilizing investment and developing policies for flood loss prevention since most flood risk reduction measures are based on cost benefit analysis. From a global or regional view‐point, it is necessary to understand relative impacts on economies of countries to mobilize international support and develop response strategies. This requires a unified approach to flood damage estimation across countries and over large spatial extents. Spatial resolutions used in the assessment have a direct impact on the estimation of potential flood heights as well as representation of property exposure and, consequently, the flood damage estimates. Using Ichinomiya river basin, Japan, as a case study, the sensitivity of spatial scale in estimating potential flood economic damages is investigated and approaches are delineated to reduce errors arising from coarse spatial resolutions. [Correction added on 5 May 2016, after first online publication: in the first sentence of the abstract the word "is" has been inserted between "it" and "useful".]